Selection of optimum conditions of biosynthesis of antibiotics of the wide range of action, active against multiresistant conditionally pathogenic infectious agent (Experimental biology, 2015)
Volumes of annually carried out chemical measures against locusts in the southeast of republic of Kazakhstan reach 120 000 hectares, at biological efficiency of insecticides from various groups of chemical compounds of 95,6-98,9 %. At the same time the death of useful entomofauna is observed. Application of a preparation form of an entomopathogenic fungi Beauveria bassiana (Bals)Vuill. in the form of oil suspension caused death of 71,0-97,5 % of the pest that is rather effective for control of locust number.
Keywords: аctinomycetes; antibiotics; cultural liquid; multiresistant test microorganisms; biomass; mycelium; antimicrobic activity